Determinants of Obesity among University Students at UIN Alauddin Makassar - Dwi Santy Damayati; Dian Ihwana; Yessy Kurniati; Anggun Rusyantia (Journal of Indonesia Applied Nutrition (JIAN), 2026)
Obesity remains a public health and nutritional problem in Indonesia. University students are a vulnerable group prone to unhealthy lifestyles that may increase the risk of obesity. Lifestyle factors associated with obesity among students include sleep duration, risky dietary patterns, and physical activity. This study aimed to analyze the association between sleep duration, risky dietary patterns, and physical activity with obesity among students at Universitas Islam Negeri Alauddin Makassar. A cross-sectional study design was conducted among all active students registered in the university database (n = 20,805). A total of 378 participants were selected using stratified random sampling. Anthropometric measurements, including height and weight, were performed to determine obesity status. Data were collected using questionnaires on respondent characteristics, risky food consumption, dietary patterns, physical activity, and sleep quality assessed using the Pittsburgh Sleep Quality Index (PSQI). Hypothesis testing was conducted using the chi-square test and Spearman correlation with a significance level of α = The results showed that the prevalence of obesity among respondents was 18.0%. The majority of respondents (88.4%) had a sleep duration of less than 8 hours. There was a significant association between sleep duration and obesity incidence (p < 0.05; r = -0.192), although the correlation was weak. In addition, risky dietary patterns were also significantly associated with obesity (p < 0.05; r = 0.131), with a very weak correlation. In contrast, no significant association was found between physical activity and obesity (p = 0.743). Improving determinant factors associated with obesity among students may serve as an alternative approach for implementing healthy lifestyle interventions in the university setting.